Jovens leitores e leituras: um estudo de suas trajetórias - Alves, Rozeli Frasca Bueno (2008)
This research was focused on the study of the reading habits of young high school students of a public school in São Paulo, pointed by their teachers as good readers based on the facts that they were very assiduous on proposed reading activities and a constant presence at the school s library. Because teachers would often say that children who are at early ages very interested in reading, later grow to hate it and repel all reading activities, this paper aims to understand how good-readers teenagers acquire and keep their reading habits. For that purpose, we did some studies on the avaluation of reading abilities, recent public policy towards reading, the role of some educational institutions, mainly schools and their political and pedagogical proposal, with their promoting reading programs, searching for an answer to young people s reading expectations. Students told their reading history during interviews which were recorded. Based on the own reading history told by some famous brazilian writers, the following aspects were extracted and employed as the basis for the analysis: the very first contacts with reading; the reasons for reading; the accessibility to books and encouragement towards reading; what they read and why and for what purpose. The analysis of the results brought to attention the need for the formulation of new public policies promoting reading and the dissemination of communities of readers, so that this and other cultural practices can be expanded and socialized, hopefully resulting in many different choices and attitudes towards reading material